Exploratory analysis of intensified conditioning as first line treatment for patients with high risk multiple myeloma. Issue 4 (29th July 2020) - Bommier, Côme; Talbot, Alexis; Harel, Stéphanie; Cuccuini, Wendy; Gérard, Laurence; Arnulf, Bertrand
Abstract: Multiple myeloma has extremely heterogeneous outcomes. Among prognostic factors, t(4;14) and del(17p) are rare oncogenic events associated with very poor prognosis. In an exploratory case‐control study, we compared the combination of Busulfan‐Melphalan or TBI‐Melphalan with high dose Melphalan as a conditioning regimen in a series of 48 patients with del(17p) or t(4;14). These regimens were preceded by a Bortezomib‐containing induction. Progression‐free survival (PFS) was the primary endpoint whereas overall survival (OS) and complete response (CR) rate were the secondary endpoints. Twenty consecutive cases of high‐risk myeloma received a reinforced conditioning regimen of Busulfan 0.8 mg/kg x4/j IV from day‐6 to day‐3 pre‐ graft (BuMel) or total body irradiation (TBI) 12 Gy (TbiMel), having received Melphalan 140 mg/m 2 at day‐2 pre‐graft. These cases were matched to 28 controls treated with Melphalan 200 mg/m 2 at day‐2 (Mel200). After intensification ± consolidation, with a median follow‐up of 6.3 years, the CR rate was higher in the BuMel/TbiMel group (65% vs 50%, P = .006). No differences were observed between both groups in terms of PFS and OS ( P = .96). PFS in patients with a del(17p) mutation tended to be superior in the BuMel/TbiMel group. Our exploratory study shows that reinforcing the intensification regimen with Busulfan or TBI does not seem to improve the prognosis associated to t(4;14) and del(17p) abnormalities.